Tinidazole as a prophylactic agent in hysterectomy a clinical and pharmacokinetic comparison with metronidazole - Seligman, S A (Interim guidelines for the control of infections with Vero cytotoxin producing Escherichia coli (VTEC). Subcommittee of the PHLS Working Group on Vero cytotoxin producing Escherichia coli (VTEC), 1981)
The efficacy of 2 g tinidazole pre-operatively in the prevention of anaerobic sepsis following the operation of hysterectomy in 50 women was compared with that of different regimens of metronidazole. The blood levels of tinidazole at and following operation were estimated, indicating a half-=life of 13.5 hours. Clinically, the activity of tinidazole paralleled that of metronidazole for comparable blood levels. Using the data obtained, an optimum dose scheme has been calculated for tinidazole